2014
DOI: 10.1016/j.archoralbio.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of locus Xq25.1-27-2 for a low caries experience phenotype

Abstract: Objective The purpose of this study was to fine map the locus Xq25.1-27-2 in order to identify genetic contributors involved in low caries experience. Design Seventy-two families from the Philippines were studied. Caries experience was recorded and genomic DNA extracted from peripheral blood was obtained from all subjects. One hundred and twenty-eight polymorphisms in the locus Xq25.1-27-2, a region that contains 24 genes, were genotyped. Association between caries experience and alleles was tested using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Studies of genetic mechanisms in the aetiology of caries encompass, primarily, 4 main groups of genes responsible for (1) development of the enamel, (2) formation and composition of saliva, (3) immunological response, and (4) carbohydrate metabolism [Shuler, 2001;Darshana et al, 2014]. Genome-wide scan studies conducted by Vieira et al [2008] revealed the association of loci 5q13.3, 14q11.2, and Xq27.1 with low caries vulnerability, which was confirmed later by Shimizu et al [2013] and Küchler et al [2014]. On the other hand, loci 13q31.1 and 14q24.3 were connected with high caries susceptibility .…”
mentioning
confidence: 70%
“…Studies of genetic mechanisms in the aetiology of caries encompass, primarily, 4 main groups of genes responsible for (1) development of the enamel, (2) formation and composition of saliva, (3) immunological response, and (4) carbohydrate metabolism [Shuler, 2001;Darshana et al, 2014]. Genome-wide scan studies conducted by Vieira et al [2008] revealed the association of loci 5q13.3, 14q11.2, and Xq27.1 with low caries vulnerability, which was confirmed later by Shimizu et al [2013] and Küchler et al [2014]. On the other hand, loci 13q31.1 and 14q24.3 were connected with high caries susceptibility .…”
mentioning
confidence: 70%
“…1) are flanking FGF13. Originally [Vieira et al, 2008], we found linkage with Xq25.1-27.2, and the fine-mapping of the locus [Küchler et al, 2014] suggested association with FGF13, but after sequencing the coding regions of the gene, we did not find any causative mutations. Interestingly, the results of the present study showed association with markers flanking FGF13.…”
Section: Discussionmentioning
confidence: 98%
“…After the initial mapping of chromosome X as potentially involved in caries experience [Vieira et al, 2008] and an inconclusive set of results attempting to fine-map the locus [Küchler et al, 2014] role of chromosome X in dental caries may be more evident under specific dietary conditions. According to the UCSC Genome Browser, the locus that we studied has 88 genes, and the statistically associated markers (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caries is a clinical and etiological heterogeneous condition 1 and is a major oral health problem in most industrialized countries. 2 Caries can present as a cavitated lesion, or as a non-cavitated lesion, also referred to as a white spot lesion (WSL).…”
Section: Introductionmentioning
confidence: 99%